Seeking a Better Paper Trail of Federal Research Funding - Bendicksen, Liam; Kesselheim, Aaron S; Feldman, William B (JAMA : the journal of the American Medical Association, 2024)
This work discusses initiatives designed to capture the value of public investment that will result in an accurate, comprehensive, and transparent paper trail of public funding.